Knowledge of blood transfusion practice among nurses in Hospital Universiti Sains Malaysia - Saad, Nor Hafiza (2016)
Blood transfusion is a routine medical procedure that is highly effective and potentially life-saving treatment for many patients. However, blood transfusion procedure is not without a risk. It may lead to a major morbidity and mortality. Therefore, nurses’ skill and knowledge are very crucial to assure safe transfusion practice. This study was carried out to assess nurses’ knowledge on the blood transfusion procedures, including knowledge on complication of blood transfusion. A descriptive study was done involving a random sample of 200 nurses involved in blood transfusion in HUSM. A validated modified version of Routine Blood Transfusion Knowledge Questionnaire (RBTKQ) was used. The questionnaires were completed by the nurses in the presence of the researcher. Each correct response was awarded one point. No point was awarded if two conflicting responses were selected. Our nurses overall knowledge score were average with the mean of 54.88% (range 30.36- 73.2). There was significant association of knowledge score with the frequency of performing blood transfusion. However, no significance association between knowledge score and other factors such as gender, academic qualification, duration of working experience and type of wards. Even when comparing between those who had receive training in blood transfusion and those who not, there was no significant difference of knowledge score between them. In conclusion, the nurses had significant knowledge deficits of blood transfusion process. Since good awareness of blood transfusion procedure and complications among nurses could avoid transfusion error and adverse reaction as well as assuring patients’ safety, there is a need for a compulsory on-going educational and training program to improve their knowledge with complimentary regular audit program.